1988
DOI: 10.1128/aac.32.8.1223
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of teicoplanin in pediatric patients

Abstract: The pharmacokinetics of teicoplanin have been studied in 13 pediatric male patients from 2 to 12 years of age. Patients were given a single 3-mg/kg intravenous dose of teicoplanin for prophylaxis. Blood and urine samples were collected for 8 days after administration, and teicoplanin levels were determined by microbiological assay. Pharmacokinetic parameters were estimated from a three-compartment open pharmacokinetic model and from a noncompartmental analysis. Levels in plasma 1 h after the administration ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 15 publications
(25 reference statements)
2
12
0
Order By: Relevance
“…Great variation for PK parameters of teicoplanin was presented in children. The typical population values of CL in our study (0.014 L/h/kg) was similar to the range of 0.015-0.024 L/h/kg reported in non-PICU Caucasians previously, but lower than that in PICU Caucasians (0.03-0.074 L/h/kg) (Aarons et al, 1998;Lukas et al, 2004;Ramos-Martin et al, 2014;Reed et al, 1997;Sanchez et al, 1999;Terragna et al, 1988;Zhao et al, 2015). Due to widespread systemic inflammation, patients may often have an ARC in PICU patients (Van Der Heggen et al, 2019), and increased volume of distribution and drug clearance has been observed for hydrophilic drugs, resulting in sub-therapeutic trough concentrations (Hirai et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Great variation for PK parameters of teicoplanin was presented in children. The typical population values of CL in our study (0.014 L/h/kg) was similar to the range of 0.015-0.024 L/h/kg reported in non-PICU Caucasians previously, but lower than that in PICU Caucasians (0.03-0.074 L/h/kg) (Aarons et al, 1998;Lukas et al, 2004;Ramos-Martin et al, 2014;Reed et al, 1997;Sanchez et al, 1999;Terragna et al, 1988;Zhao et al, 2015). Due to widespread systemic inflammation, patients may often have an ARC in PICU patients (Van Der Heggen et al, 2019), and increased volume of distribution and drug clearance has been observed for hydrophilic drugs, resulting in sub-therapeutic trough concentrations (Hirai et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…The clinical utility of the opportunistic sampling design is undoubtedly in paediatric pharmacokinetic studies. In the present study, the median estimated volume of distribution at steady‐state was 1.1 l kg –1 , which was consistent with previous pharmacokinetic studies of teicoplanin in children using rich pharmacokinetic sampling design and non‐compartment pharmacokinetic analysis .…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly bound to albumin (90%) and eliminated predominantly by the kidney . Some pharmacokinetic studies of teicoplanin have been conducted in children , however, only in children without HM. As demonstrated in our previous pharmacokinetic study of vancomycin, eight children with HM represent an identified sub‐population of patients with proper pharmacokinetic parameters, different from other paediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…A three-compartment model was selected to describe teicoplanin disposition [18]. The terminal half life of teicoplanin in children being 57.9 h (SE 4.16) [22], and in order to obtain as much information as possible, we derived the pharmacokinetic parameters by fitting the whole medication history of each patient. Unfortunately, some babies apparently did not receive the prescribed dose, despite the fact that the drug administration procedure was carefully explained to the nurses.…”
Section: Discussionmentioning
confidence: 99%